Vote choices and valence: intercepts and alternate specifications - Mauerer, Ingrid Doris; Tutz, Gerhard (Cambridge University Press, 2024)
Valence is a crucial concept in studying spatial voting and party competition. The widely adopted approach is to rely on intercepts of vote choice models and to infer, based on their size and direction, how valence affects party strategies in empirical settings. The approach suffers from fundamental statistical flaws. This contribution provides the statistical fundamentals to advance the empirical modeling of valence. It proposes an appropriate modeling approach to interpret intercepts as valences and alternate specifications to parameterize the effects of valence.
Keywords: Estadística; Codificación; Valence; Choice model; Intercepts; Coding; Chooser attributes; Choice attributes